OMOTENASHI: BUDAYA KERAMAHTAMAHAN DI JEPANG (AKAR BUDAYA DAN MANIFESTASINYA) - Lina Rosliana (Diponegoro University, 2018)
(Title: Omotenashi: Hospitality Culture in Japan, Its Culture’s Root and Manifestacy) When visiting Japan, we will be able to feel the true meaning of the slogan